Upaya Meningkatkan Hasil Belajar dan Aktivitas Siswa Menggunakan Cooperative Learning Tipe Jigsaw di Kelas IV Sekolah Dasar - Fenia Reny DA (Universitas Negeri Padang, 2020)
The purpose of this research is to improve the learning results and activities of students in mathematics subjects namely grade IV SD Negeri 199 Palembang with Cooperative Learning Type Jigsaw model. Researched using class action research methods. The problems in this study are whether the use of The Jigsaw Type Cooperative Learning model can improve the math learning outcomes of grade IV students of SD Negeri 199 Palembang and how students activity towards the use of Cooperative Learning Model Type Jigsaw used by researchers. The subject is a student in a class of 28 people. The data collection techniques used are tests and observations. Data obtained by the average result was 61.8 at the time before the improvement, an increase of (15.5%) to 71.4 in cycle I, and up again (22.9%) 87.7 in cycle II. Meanwhile, student activity in cycle I is 57%. increased to 93% in cycle II.